Islamic Architectural Styles as Stimulus in Designing Schools: Applied Field Research for Primary Schools in Jordan - Arabasi, Mazen; Al_Khattat, Ashraf (Dirasat: Human and Social Sciences, 2023)
Objectives: This research dealt with educational buildings from a functional and aesthetic point of view, where the first contact is formed for the student, and since the first impressions last, the external shape of the school is the first thing that the student comes into contact with, so the shape had to carry with it comfort and pleasure, to facilitate He has to accept the curricula himself highly, and since the inherited Islamic architectural styles are flourishing with their beautiful architectural vocabulary, the research aims to integrate them with the shape of the school, which will achieve a distinctive type of school forms in Jordan, and give the student joy and pleasure, which will be positively reflected on his educational achievement. Methods: The research followed the historical and descriptive approaches by describing the historical Islamic architecture. Results: The research concluded to prove the hypothesis of the study, as the use of Islamic architectural elements in the buildings of basic schools endears the student to the school, as well as to the importance of using the Islamic architectural style, especially the basic ones. Conclusions: The researcher recommended incorporating a minimal Islamic style in schools, as determined by a specialized committee from the Ministry of Education.